Article 299 of the Polish Code of Commercial Companies in Termsof Subject, Object and Time - Łukawski, Michał (Artykuł 299 Kodeksu spółek handlowych w ujęciu podmiotowym, przedmiotowym i temporalnym, 2024)
Article 299 of the Commercial Companies Code is a regulation securing the interests of the creditor in the event of non-payment of an obligation by a limited liability company. In the case of a valid statement of ineffectiveness of enforcement proceedings by a Court Bailiff, the creditor has the right to bring an action against the members of the management board of the debtor company whose term of office fell during the period when the claim arose or was due. The described regulation refers primarily to public and private law monetary benefits derived from various titles such as laws, contracts, etc. This article is based on a dogmatic-legal research method.
Ekonomia XXI Wieku = Economics of the 21st Century, 2024, Nr 27, s. 20-29
Keywords: company; creditor; debtor; enforceability; enforcement; spółka; wierzyciel; dług; wymagalność; egzekucja